Dispersion Mechanism and Sensitivity Analysis of Coral Sand - Xiang Cui; Ru Qu; Mingjian Hu (Journal of Marine Science and Engineering, 2025)
A lime–sand island–reef formation has a dual structure consisting of an overlying loose or weakly consolidated coral sand (CS) layer and an underlying reef limestone layer. The coral sand layer is the sole carrier of the underground freshwater lens in the lime–sand island–reef, and it differs in terms of its hydraulic properties from common terrigenous quartz sand (QS). This study investigated the mechanism of freshwater lens formation, dominated by solute dispersion, combining multi-scale experiments and numerical simulations (GMS) to reveal the control mechanisms behind the dispersion properties of coral sand and their role in freshwater lens formation. Firstly, the dispersion test and microscopic characterization revealed the key differences in coral sand in terms of its roundness, roughness, particle charge, and surface hydrophilicity. Accordingly, a hierarchical conversion model for the coral sand–quartz sand coefficient of dispersion (COD) was established (R2 > 0.99). Further, combining this with numerical simulation in GMS revealed that the response pattern of the coefficient of dispersion to key parameters of freshwater lens development is as follows: freshwater appearance time > steady-state freshwater body thickness > steady-state freshwater reserve > lens stabilization time. These results clarify the development mechanism and formation process behind freshwater lenses on island reefs, from the micro to the macro scale, and provide a scientific basis for optimizing the protection of freshwater resources in coral islands and guiding the construction of artificial islands.